Gram Scale Synthesis of Cuprous Oxide Nanoparticles: Dip Coating on Cellulose Filter Paper, Antibacterial Activity and Comparison with Commonly Available Face Masks - Rai, Randhir (Asian Journal of Chemistry, 2023)
Cuprous oxide nanoparticles (Cu2ONPs) were synthesized on a gram scale via bottom-up approach without making use of any hazardous stabilizing agent. The nanoparticles were coated on qualitative cellulose filter paper via dip coating method. UV-Vis spectroscopy, Powder X-Ray diffraction (PXRD) and electron microscopy were used to characterize Cu2ONPs and Cu2ONPs coated filter paper (Cu2ONPs-FP). The antibacterial activity of Cu2ONPs-FP was studied against E. coli DH5α and compared with commonly accessible face masks.